2015
DOI: 10.1631/jzus.b1500113
|View full text |Cite
|
Sign up to set email alerts
|

潜在候选细胞构建组织工程的泪道上皮: 兔的组织学和细胞学研究

Abstract: Abstract:Objective: Injury and deficiency of the lacrimal duct epithelium (LDE) can lead to a variety of lacrimal diseases. The purpose of this study was to characterize potential candidate cells for constructing a tissue-engineered LDE. Methods: Different areas of the conjunctiva and lacrimal duct tissue were removed from male adult New Zealand white rabbits for histological evaluation. Hematoxylin and eosin staining and immunohistochemical staining of cytokeratin AE1+AE3, cytokeratin 4, Ki-67, and MUC5AC wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This forces us to search for other alternatives. One such alternative can be found within the human lacrimal drainage system, consisting of lacrimal puncta, lacrimal canaliculi, common canaliculus, lacrimal sac, and nasolacrimal duct, which plays an important role in draining extra tear fluid into the inferior meatus of the nose 17 , 41 . Our data in this study showed that most of the lacrimal canaliculi had normal epithelial layers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This forces us to search for other alternatives. One such alternative can be found within the human lacrimal drainage system, consisting of lacrimal puncta, lacrimal canaliculi, common canaliculus, lacrimal sac, and nasolacrimal duct, which plays an important role in draining extra tear fluid into the inferior meatus of the nose 17 , 41 . Our data in this study showed that most of the lacrimal canaliculi had normal epithelial layers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LGSCs (Abughanam et al, 2019;Ali et al, 2017;Xiao & Zhang, 2020;Xie et al, 2015;Zoukhri et al, 2008) and side population cells (Mishima et al, 2012). One study (Jeong et al, 2021) evaluated the SC component in LG organoids cultured in vitro (Tables 2 and 3).…”
Section: Stem Cell Markers Employed In Studiesmentioning
confidence: 99%
“…The remaining 25 studies included in this review investigated the development of new drug targets and therapies or focused on direct LG regeneration using SCs from various sources (Table 1). Studies were published between June 2008 (Zoukhri et al, 2008) and September 2020 (Yu et al, 2020) in the United States (Ali et al, 2017; Aluri et al, 2017; Basova et al, 2017; Gromova et al, 2017; Lu et al, 2017; You et al, 2012; Zoukhri et al, 2008), China (Liu, 2017; Xiao & Zhang, 2020; Xie et al, 2015; Yu et al, 2020; Zhang et al, 2014), Germany (Dietrich, Ott, et al, 2019; Dietrich, Roth, et al, 2019; Roth et al, 2015), Canada (Abughanam et al, 2019; Yao et al, 2019), Japan (Hirayama et al, 2013; Mishima et al, 2012), Denmark (Moller‐Hansen et al, 2020), Korea (Jeong et al, 2021; Lee et al, 2015), Brazil (Bittencourt et al, 2016), Spain (Villatoro et al, 2015) and Turkey (Beyazyildiz et al, 2014) (Figure 4).…”
Section: Regeneration Of the Lacrimal Gland Using Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations